Speed control of DC motor using PI controller - Mohs Azri, Abd Mutalib (2008)
The development of technologies affects the demands of industries at the present time. Thus, automatic control has played a vital role in the advance of engineering and science. In today’s industries, control of DC motors is a common practice. Therefore, implementation of DC motor controller is required. There are many types of controller that can be used to implement the elegant and effective output. One of them is by using a PI controller. PI stands for Proportional and Integral Controllers which are designed to eliminate the need for continuous operator attention thus provide automatic control to the system. Cruise control in a car and a house thermostat are common examples of how controllers are used to automatically adjust some variable to hold the measurement (or process variable) at the set-point. This project is focusing on implementing PI controller to control speed of a dc motor. The overall project is divided into two parts. The first part is concern on the simulation using MATLAB simulink where the dc motor is modeled and PI controller is tuned using Ziegler-Nichols rules and software tuning. The second part is implementing the simulation. This part is divided into another two parts, Graphical User Interface (GUI) development and hardware interfacing. GUI is built using National Instrument LabVIEW software with implementation of PI controller. An oscilloscope also had been build there. Hardware interfacing part is built with Mitsumi dc mini-motors, M31E-1 Series, speed sensor and analog to digital converter, DAC8032. As the result, PI controller is capable to control the speed of dc motor followed the result from simulation.